Crystal Structure of the Chloroplastic Glutamine Phosphoribosylpyrophosphate Amidotransferase GPRAT2 From Arabidopsis thaliana - Cao, Xueli; Du, Bowen; Han, Fengjiao; Zhou, Yu; Ren, Junhui; Wang, Wenhe; Chen, Zeliang; Zhang, Yi (Frontiers in Plant Science, 2020)
Chloroplastic glutamine phosphoribosylpyrophosphate amidotransferase (GPRATase) catalyzes the first step of de novo purine biosynthesis in Arabidopsis thaliana, and DAS734 is a direct and specific inhibitor of AtGPRAT, with phytotoxic effects similar to the leaf beaching phenotypes of known AtGPRAT genetic mutants, especially cia1 and atd2. However, the structure of AtGPRAT and the inhibition mode of DAS734 still remain poorly understood. In this study, we solved the structure of AtGPRAT2, which revealed structural differences between AtGPRAT2 and bacterial enzymes. Kinetics assay demonstrated that DAS734 behaves as a competitive inhibitor for the substrate PRPP of AtGPRAT2. Docking studies showed that DAS734 forms electrostatic interactions with R264 and hydrophobic interactions with several residues, which was verified by binding assays. Collectively, our study provides important insights into the inhibition mechanism of DAS734 to AtGPRAT2 and sheds light on future studies into further development of more potent herbicides targeting Arabidopsis GPRATases.